Discovery of 4-(phenoxymethyl)-1H-1, 2, 3-triazole derivatives as novel xanthine oxidase inhibitors. (15th March 2022) - Zhang, Ting-jian; Zhang, Yi; Zhang, Zhen-hao; Wang, Zhao-ran; Zhang, Xu; Hu, Sen-sen; Lu, Peng-fei; Guo, Shuai; Meng, Fan-hao
Graphical abstract: Highlights: A series of 4-(phenoxymethyl)-1 H -1, 2, 3-triazole derivatives were synthesized. Ligand efficiency metrics were monitored during structural optimization. Compound 9 m showed the best in vitro XO inhibitory potency. Molecular docking and dynamics provided a reasonable interaction mode. Compound 9 m showed potent hypouricemic effects in hyperuricemic rat model. Abstract: A series of 4-(phenoxymethyl)-1 H -1, 2, 3-triazole derivatives were designed, synthesized, and evaluated for their xanthine oxidase (XO) inhibitory activities. Among these compounds, 9m emerged as the most effective XO inhibitor with an IC50 value of 0.70 μM, which was approximately 14-fold more potent than allopurinol. Additionally, compound 9m displayed favorable drug-like properties with ligand efficiency (LE) and lipophilic ligand efficiency (LLE) values of 0.33 and 3.41, respectively. We further explored the binding mode of 9m in complex with XO by molecular docking and molecular dynamics studies. In vivo hypouricemic studies also suggested that 9m could effectively lower the serum uric acid levels of rat. In summary, compound 9m could be a promising lead for further development of XO inhibitors.